Medieval misogyny and the invention of Western romantic love - Bloch, R. Howard (University of Chicago Press, 1991)
Until now the advent of Western romantic love has been seen as a liberation from--or antidote to--ten centuries of misogyny. In this major contribution to gender studies, R. Howard Bloch demonstrates how similar the ubiquitous antifeminism of medieval times and the romantic idealization of woman actually are. Through analyses of a broad range of patristic and medieval texts, Bloch explores the Christian construction of gender in which the flesh is feminized, the feminine is aestheticized, and aesthetics are condemned in theological terms. Tracing the underlying theme of virginity from the Church.